1976
DOI: 10.1007/bf02632516
|View full text |Cite
|
Sign up to set email alerts
|

Crambe seed processing: Removal of glucosinolates by water extraction

Abstract: A method is reported for removingepi‐progoitrin, the major glucosinolate, from crambe seed meal. Defatted meal was cooked and water extracted or treated with soda ash and then water extracted. Although soda ash aided destruction and removal of glucosinolate factors, there was a 28% reduction in total lysine. In animal feeding tests designed to reflect differences due to toxic factors, soda ash treated and water extracted meals gave the best results. No toxicity was apparent in rats and chicks fed these meals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Average composition of seed grown in different geographical locations is shown in Table I, where crude protein (N • 6.25) levels range from 20% in the whole seed to nearly 50% in the dehulled, defatted meal (10)(11)(12)(13)(14)(15). Seed hull accounts for ca.…”
Section: Protein Quantity and Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Average composition of seed grown in different geographical locations is shown in Table I, where crude protein (N • 6.25) levels range from 20% in the whole seed to nearly 50% in the dehulled, defatted meal (10)(11)(12)(13)(14)(15). Seed hull accounts for ca.…”
Section: Protein Quantity and Qualitymentioning
confidence: 99%
“…VanEtten et al (8) compared the AA pattern of hen's egg to the AA patterns of a number of cereal grains and oilseed meals, and they concluded that the AA pattern and high protein content of crambe would make it a good supplemental source of protein to use with cereal grains in feeds. aAdapted from Mustakas and coworkers (10,12,14); Kirk and coworkers ( 11,13) and Baker et al (15).…”
Section: Protein Quantity and Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, crambe seeds contain glucosinolates that when hydrolyzed by an endogenous enzyme, thioglucosidase, produce toxic compounds which limit palatability to animals and render the meal toxic to nonruminants (6). Various processing methods have been developed to detoxify crambe meal by either decomposing the glucosinolates (2,7,8) or by inactivating thioglucosidase and removing the intact glucosinolates by aqueous extraction (9)(10)(11). Both dry and moist heat have been used to inactivate thioglucosidase (12).…”
Section: Introductionmentioning
confidence: 99%